Effect of Ethanolic Leaf Extract of Senna Fistula on some Haematological Parameters, Lipid Profile and Oxidative Stress in Alloxan-induced Diabetic Rats (Nigerian Journal of Physiological Sciences, 2021)
Summary: Increasing evidence in both experimental and clinical studies suggests that oxidative stress plays a major role in the pathogenesis of both types of diabetes mellitus. The disease is also known to adversely affect some haematological parameters and cause dyslipidemia. This study was designed to investigate the effect of chronic administration of ethanolic leave extract of Senna fistula on haematological values, oxidative stress and dyslipidemia in experimental diabetic rats. Twenty-four albino rats weighing 120-150 g were divided into 4 experimental groups of six rats each; control, diabetic untreated, diabetic treated with glibenclamide and diabetic treated with 100 mg/kg b.w of Senna fistula. Diabetes was induced by 100 mg/kg b.w. of alloxan monohydrates. The control and diabetic groups received normal saline while the diabetic treated groups were administered with 5mg/kg and 100mg/kg body weight of glibenclamide and ethanolic leaves extract of Senna fistula respectively for 28 days. At the end of experimental period blood samples were taken from the animals for the determination of Red blood cells (RBC), packed cell volume (PCV), Haemoglobin concentration (Hb), total cholesterol, triglycerides (TG), high density lipoprotein (HDL), low density lipoprotein (LDL) and malondialdehyde (MDA), marker of lipid peroxidation. The result showed that in diabetic rats, PCV, RBC and Hb were decreased but the application of the extract increased the parameters (P